Characterisation of Beam-to-column Steel-concrete Composite Joints Beyond Current Eurocode Provisions. (October 2019) - Demonceau, Jean-François; Ciutina, Adrian
Abstract: In EN 1994-1-1, design rules are given for the evaluation of the mechanical properties of structural steel-concrete composite joints (rotational stiffness, resistance and ductility). The proposed rules are based on the component method as recommended in EN 1993-1-8 and, in particular, rules for components specific to composite joints are provided in EN 1994-1-1. The main weakness of the rules as presently proposed is that they are only covering cases where composite joints are subjected to shear forces and hogging moments while, in practice, such joints can be subjected to other loading conditions such as sagging bending moments, cyclic loadings, combined bending moments and axial loads, elevated temperatures etc. It is the reason why, during the last decades, researches have been conducted in this field with the objective of improving/extending the rules presently recommended in the Eurocodes. This present paper highlights the main outcomes from part of these researches conducted at Liège University and at University Politehnica Timisoara which could be seen as proposals for future improvements of the beam-to-column provisions in Eurocodes in general and of Eurocode 4 in particular.